2014
DOI: 10.5194/bgd-11-7359-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for vivianite formation and its contribution to long-term phosphorus retention in a recent lake sediment: a novel analytical approach

Abstract: Abstract. Vivianite, Fe3(PO4)2 × 8 H2O, is a ferrous iron phosphate mineral which forms in waterlogged soils and sediments. The phosphorus (P) bound in its crystal lattice is considered to be immobilised because vivianite is stable under anoxic, reducing, sedimentary conditions. Thus, vivianite formation can make a major contribution to P retention during early diagenesis. Much remains unknown about vivianite in sediments, because technical challenges have rendered direct identification and quantification diff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…However, the direct identification of Fe(II) phosphate minerals, such as vivianite, is technically challenging, as demonstrated by a recent study which concluded that vivianite cannot be identified by X‐ray diffraction of bulk sediment samples (Rothe et al. ). By applying a heavy‐liquid separation to sediments, Rothe et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct identification of Fe(II) phosphate minerals, such as vivianite, is technically challenging, as demonstrated by a recent study which concluded that vivianite cannot be identified by X‐ray diffraction of bulk sediment samples (Rothe et al. ). By applying a heavy‐liquid separation to sediments, Rothe et al.…”
Section: Discussionmentioning
confidence: 99%
“…Vivianite is thought to occur at less than 1% concentration, which has made its direct identification challenging; despite this, several studies show convincing spectroscopic evidence of vivianite in lake sediments (e.g., Manning et al 1991;Fagel et al 2005;Sapota et al 2006;Rothe et al 2014). Additionally, its presence has been inferred from thermodynamic calculations (e.g., Nriagu and Dell 1974;Matisoff 1980).…”
Section: Dissolutionmentioning
confidence: 99%
“…Vivianite is known to retain phosphorus in lakes under reducing conditions in iron rich systems (Moore et al 1998;Sapota et al 2006;Rothe et al 2014). However, vivianite formation and stability in SiFe-C rich lake sediments are rarely studied (Müller and Förstner, 1973;Fagel et al 2005;Owen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, vivianite formation and stability in SiFe-C rich lake sediments are rarely studied (Müller and Förstner, 1973;Fagel et al 2005;Owen et al 2010). In addition, the quantitative contribution of vivianite to phosphorus retention has only rarely been quantified (Rothe et al 2014).…”
Section: Introductionmentioning
confidence: 99%